2D Seismic Data Reinterpretation and The Structural View of Zubair, Yamama, and Gotnia Formations in Afaq Area, Central Iraq - Hamza, Noor A.; Al-Rahim, Ali M. (Iraqi Journal of Science, 2022)
An interpretative study of the two-dimensional seismic data of the Afaq area was conducted using the Petrel 2017 software. 2D seismic reflection sections are used to give a structural interpretation of Afaq structure based on synthetic seismogram and well log data. Three reflectors, Zubair, Yamama, and Gotina Formations, were selected. These reflectors are defined from well west kifl (wk-1), Where located adjacent to the study area. Structural maps of the Zubair, Yamama, and Gotnia formations are prepared and interpreted, including TWT maps, Average velocity maps, and depth maps. The studies concluded that the Afaq structure area does not contain main faults, but secondary faults with short and limited extensions. The structure of Afaq is a Monocline structure at Zubair and turns into a semi-structure (trap structure) at the Yamama and Gotnia formations. The study also showed that the structure of Afaq is plunging structure towards the east.